Care of the Patient With Acute Ischemic Stroke (Prehospital and Acute Phase of Care): Update to the 2009 Comprehensive Nursing Care Scientific Statement. Issue 5 (May 2021) - Ashcraft, Susan; Wilson, Susan E.; Nyström, Karin V.; Dusenbury, Wendy; Wira, Charles R.; Burrus, Tamika M.
Abstract : The year 2020 was the year of the nurse, celebrating nurse scholarship, innovation, and leadership by promoting scientific nursing research, improving nursing practice, advancing nursing education, and providing leadership to influence health policy. As architects of stroke care, neuroscience nurses play a vital role in collaborating and coordinating care between multiple health professionals. Nurses improve accessibility and equity through telestroke, emergency medical services, and mobile stroke units and are integral to implementing education strategies by advocating and ensuring that patients and caregivers receive stroke education while safely transitioning through the health care system and to home. Stroke care is increasingly complex in the new reperfusion era, requiring nurses to participate in continuing education while attaining levels of competency in both the acute and recovery care process. Advanced practice nurses are taking the lead in many organizations, serving as prehospital providers on mobile stroke units, participating as members of the stroke response team, and directing stroke care protocols in the emergency department. This scientific statement is an update to the 2009 "Comprehensive Overview of Nursing and Interdisciplinary Care of the Acute Ischemic Stroke Patient." The aim is to provide a comprehensive review of the scientific evidence on nursing care in the prehospital and hyperacute emergency hospital setting, arming nurses with the necessary tools to provide evidenced-based high-quality care. Abstract : Supplemental Digital Content is available in the text.